2021
DOI: 10.1016/j.celrep.2021.109145
|View full text |Cite
|
Sign up to set email alerts
|

GATA6 defines endoderm fate by controlling chromatin accessibility during differentiation of human-induced pluripotent stem cells

Abstract: GATA6 defines endoderm fate by controlling chromatin accessibility during differentiation of human-induced pluripotent stem cells Graphical abstract Highlights d Newly accessible chromatin in definitive endoderm is enriched for GATA motifs d Definitive endoderm patterning is significantly perturbed in GATA6 À/À cells d GATA6 interacts with multiple chromatin remodeling complexes d GATA6-dependent patterning commonly precedes the onset of gene expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…GATA6 is reported to be a pioneer factor that directly binds to non-permissive heterochromatin and primes the opening of chromatin and histone modifications by interacting with the chromatin remodeling complex 37 . DNA demethylation by GATA6 may be a step toward pioneering.…”
Section: Discussionmentioning
confidence: 99%
“…GATA6 is reported to be a pioneer factor that directly binds to non-permissive heterochromatin and primes the opening of chromatin and histone modifications by interacting with the chromatin remodeling complex 37 . DNA demethylation by GATA6 may be a step toward pioneering.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that transcription factors are induced at precisely controlled stages of development to establish lineage-specific transcriptional profiles. Emerging evidence has highlighted that the capacity of a transcription factor to occupy its target binding sites is dependent on external parameters, such as chromatin state and the presence of additional transcription factors ( Cernilogar et al., 2019 ; Donaghey et al., 2018 ; Fernandez Garcia et al., 2019 ; Heslop et al., 2021 ; Lee et al., 2019 ). Although the availability of additional regulators is known to influence the binding profile of a transcription factor, the molecular basis of these interactions remains incompletely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work using iPSCs as a model of early foregut development revealed that GATA6 is essential for definitive endoderm formation ( Chia et al., 2019 ; Fisher et al., 2017 ; Shi et al., 2017 ; Tiyaboonchai et al., 2017 ). Moreover, we subsequently reported that GATA6 is required to establish the accessible chromatin profile within the definitive endoderm, thereby permitting developmental progression ( Heslop et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liver specification remains a complex stage of development, as hepatic induction is not directed by a single master regulator but is instead controlled by the concerted action of multiple transcription factors. In the endoderm, FOXA1/2/3, GATA4 and GATA6 act as pioneer factors, creating accessible chromatin and coordinating sequential binding with HNF4α during hepatic induction (Heslop et al, 2021;Horisawa et al, 2020). In support of this, combined deletion of Foxa1 and Foxa2 from foregut endoderm prevents liver bud formation (Lee et al, 2005), suggesting that FOXA factors are essential for liver specification.…”
Section: Keymentioning
confidence: 93%
“…In support of this, combined deletion of Foxa1 and Foxa2 from foregut endoderm prevents liver bud formation (Lee et al, 2005), suggesting that FOXA factors are essential for liver specification. Similarly, deletion of GATA6 from pluripotent stem cells perturbs binding of FOXA2 and hepatic specification from definitive endoderm (Heslop et al, 2021). Although it is clear that FOXA and GATA factors are essential regulators of hepatic lineage induction, neither are sufficient on their own and additional transcription factors are required.…”
Section: Keymentioning
confidence: 99%